Synthesis of Hierarchical Porous SAPO-34 and Its Catalytic Activity for 4,6-Dimethyldibenzothiophene - Wang, Hua-Qin; Cui, Yun-Qi; Ding, Ya-Long; Xiang, Mei; Yu, Pei; Li, Rong-Qiang (Frontiers in Chemistry, 2022)
Zeolite SAPO-34 has been widely used in the industry because of its special pore structure and wide distribution of acid sites in the pore channel. However, traditional SAPO-34 with a small pore size suffers from carbon deposition and deactivation in catalytic reactions, and its inability to catalytically convert bulky organic molecules limits its industrial application. Meanwhile, impurities of SAPO-5, which have weak acidity leading to rapid catalyst deactivation, appear in SAPO-34 zeolite. Therefore, it is of great significance to synthesize SAPO-34 zeolite with a mesoporous pore structure, which can significantly improve the transfer of molecules in zeolites. In this paper, SAPO-34 zeolite with a hierarchical pore structure was synthesized, and its hydrodesulfurization performance for 4,6-dimethyldibenzothiophene (4,6-DMDBT) was studied in a fixed bed reactor. The characteristic results show that BET-specific surface area, micropore volume, and mesoporous volume of synthesized SAPO-34 are 754 m2 g−1, 0.25, and 0.23 cm3 g−1 respectively, and the pore size is mainly concentrated at 4 nm. The catalytic conversion of 4,6-DMDMT with Co- and Mo-supported SAPO-34 is about 83%, which is much higher than the catalytic performance of Al2O3.